"COLOR COMBINATION IN ABSTRACT PAINTING STYLE": “अमूर्त चित्रकला शैली में रंग संयोजन“ - Bhardwaj, Kumkum; Yadav, Monika (International Journal of Research -GRANTHAALAYAH, 2014)
Varna means color is the life of any artwork which depends on vision and light, there is some color in every object, so any object is identified by colors. Color is the property of light. Color does not exist independently, but the effect that the brain has on the axon is color. Two objects of the same form are identified by different colors. Color is the property of the object that we experience by the eyes. We can see an object only in the presence of light, so light gives us a sense of colors. वर्ण अर्थात रंग किसी भी कलाकृति का प्राण है जो दृष्टि एवं प्रकाश पर निर्भर करता है प्रत्येक वस्तु में कोई न कोई रंग विद्यमान होता है अतः किसी भी वस्तु की पहचान रंगों के कारण होती है। रंग प्रकाश का गुण है रंग का स्वतंत्र अस्तित्व नहीं होता है अपितु अक्षपटल द्वारा मस्तिष्क पर पड़ने वाला प्रभाव रंग है एक ही रूप की दो वस्तुओं को पृथक-पृथक रंगों द्वारा पहचाना जाता है रंग वस्तु का वह गुण है जिसका अनुभव हम नेत्रों द्वारा करते है प्रकाष की उपस्थिति में ही हम किसी वस्तु को देख सकते है अतः प्रकाश हमें रंगों का बोध कराता है।